Pycnogonida (Arthropoda) from Northern Adriatic Corallina officinalis Linnaeus, 1758 belts - LEHMANN, TOBIAS; SPELDA, JÖRG; MELZER, ROLAND; BURŠIĆ, MOIRA (Mediterranean Marine Science, 2021)
We studied Pycnogonida, sea spiders, collected from 54 samples of Corallina officinalis belts in the vicinity of Pula and the Brijuni National Park representing both exposed and sheltered localities as well as different levels of human impact. Seven species were identified, namely Achelia echinata, A. langi, Tanystylum conirostre, Anoplodactylus angulatus, A. pygmaeus, Trygaeus communis, and Callipallene tiberi. As we used a quantifiable standard sample size of 5 cm2, we could perform a statistical analysis of species richness and abundances. The exposed low human impact sites showed a significantly higher amount of both, specimens and species than the sheltered high impact sites. C. tiberi and A. echinata showed a significant preference for exposed low impact sites while T. conirostre was equally distributed among the habitat subtypes.